VD_FINDINFO HC / 2012 / 429 vom 16. August 2012 - VD Tribunal cantonal (2012)
ACTION EN DIVORCE, LITISPENDANCE, CONCLUSIONS, DÉLAI DE RECOURS, COMPÉTENCE INTERNATIONALE, ENFANT, ASSISTANCE JUDICIAIRE, DROIT TRANSITOIRE | 120 al. 3 CPC, 124a CPC, 461 al. 1 let. b CPC, 65 al. 1 LDIP, 85 al. 1 LDIP, 85 al. 4 LDIP, 9 al. 1 LDIP, 5 CLaH 96